FORMATION AND DEVELOPMENT OF INFRASTRUCTURE OF INNOVATION ACTIVITY - Anna V. Raikhlina (Статистика и экономика)
The author presents the research results of problems of the efficiency of the existent innovation structure and offers one of the feasible directions of their solving via formation and development of an infrastructure system of innovation activities.